2022
DOI: 10.3390/pharmaceutics14061259
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Technological Factors on the Quality of Chitosan Microcapsules with Boswellia serata L. Essential Oil

Abstract: Essential oils contain many volatile compounds that are not stable and lose their pharmacological effect when exposed to the environment. The aim of this study is to protect Boswellia serrata L. essential oil from environmental factors by encapsulation and determine the influence of chitosan concentration and types (2%, 4%; medium and high molecular weights), essential oil concentration, different emulsifiers (Tween and Span), and technological factors (stirring time, launch height, drip rate) on the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Moreover, chitosan with a relatively low molecular weight was used to modify the coatings (a viscosity of 10 cps measured for 1% solution in 1% acetic acid), while the hardness of chitosan-based materials is significantly affected by the molecular weight of a polymer. 30 Under the conditions of the coating cross-linking process, the epoxy groups derived from acrylic resin may react with the amino or hydroxyl groups of chitosan, causing its cross-linking, which increases its hardness. 31 However, the protonated nitrogen atoms in chitosan will not easily react with the epoxy groups during the cationic photopolymerization process due to their positive charge.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, chitosan with a relatively low molecular weight was used to modify the coatings (a viscosity of 10 cps measured for 1% solution in 1% acetic acid), while the hardness of chitosan-based materials is significantly affected by the molecular weight of a polymer. 30 Under the conditions of the coating cross-linking process, the epoxy groups derived from acrylic resin may react with the amino or hydroxyl groups of chitosan, causing its cross-linking, which increases its hardness. 31 However, the protonated nitrogen atoms in chitosan will not easily react with the epoxy groups during the cationic photopolymerization process due to their positive charge.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Addition of chitosan results in a decrease in the relative hardness compared to the reference sample based on acrylic resin, which is due to the lower hardness of chitosan compared to the cross-linked acrylic matrix. Moreover, chitosan with a relatively low molecular weight was used to modify the coatings (a viscosity of 10 cps measured for 1% solution in 1% acetic acid), while the hardness of chitosan-based materials is significantly affected by the molecular weight of a polymer …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many researchers have chosen natural polymer materials as wall materials. Among them, chitosan is one widely used wall material [16]. The results showed that different molecular weights and concentrations of chitosan had significant effects on the texture and appearance of microcapsules.…”
Section: Introductionmentioning
confidence: 99%